1974
DOI: 10.1136/pgmj.50.588.603
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal food poisoning and botulism

R J Gilbert

Abstract: SummaryStaphylococcal food poisoning and botulism are caused by the ingestion of food containing exotoxins. Outbreaks of both are still a problem in many countries. This paper attempts to summarize information relating to these illnesses, together with advice on how their incidence may be reduced, or better still prevented.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
4

Year Published

1978
1978
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 44 publications
0
4
0
4
Order By: Relevance
“…Contamination of food with staphylococcus causes gastrointestinal illness of sudden illness because the organism was found to be capable of producing an enterotoxin. The food normally implicated in staphylococcus food poisoning is meat and its products [9, 11, 12]. Our findings therefore suggest staphylococcus aureus food poisoning.…”
Section: Discussionmentioning
confidence: 62%
“…Contamination of food with staphylococcus causes gastrointestinal illness of sudden illness because the organism was found to be capable of producing an enterotoxin. The food normally implicated in staphylococcus food poisoning is meat and its products [9, 11, 12]. Our findings therefore suggest staphylococcus aureus food poisoning.…”
Section: Discussionmentioning
confidence: 62%
“…Fortunately, botulism is rare in this country. Few incidents have been reported since the largest reported outbreak in 1922 at Loch Maree in Scotland when eight people died after eating sandwiches made from wild duck paste (Gilbert 1974). The spores of Cl.…”
Section: Incidence Of Food Poisoningmentioning
confidence: 99%
“…Hobbs (1962) reported that the number of organisms needed to produce this amount of toxin is 5 x lo5 to 1 x 106 of food. However estimates of the mimimum amount of staphylococcal enterotoxin necessary to cause illness range from 0.015 to 0.35 pg enterotoxin/kg bodyweight (Gilbert, 1974). The relationship between toxin concentration, body weight and illness highlights the potential dangers to underweight patients and particularly children on enteral feeds.…”
Section: Significance Of Contaminationmentioning
confidence: 99%